Integrasi Nahwu, Sharaf, dan Balaghah sebagai Kerangka Linguistik Arab Klasik serta Implikasinya terhadap Pendidikan Bahasa Arab Modern - Maftukh Ghulam Mursyidan; Muhammad Nu'man; Anisah Firdausi Nuzula (SURAU : Journal of Islamic Education, 2026)
This study examines the theoretical construction of three classical Arabic linguistic disciplines—nahwu (syntax), sharaf (morphology), and balaghah (rhetoric)—and their relevance to contemporary Arabic language education. Previous studies have generally discussed these disciplines separately, focusing either on grammatical structures, morphological systems, or rhetorical aspects, with limited attention to their integrated contribution to modern Arabic pedagogy. Addressing this gap, the present study aims to develop a comprehensive understanding of how these disciplines collectively function as a pedagogical foundation for Arabic language learning in the twenty-first century. Employing a descriptive qualitative approach and library research methodology, the study analyzes classical sources, including Sibawayh’s al-Kitāb, al-Farahīdī’s Kitāb al-ʿAyn, and al-Jurjānī’s Dalāʾil al-Iʿjāz, alongside contemporary literature on Arabic language teaching. The findings indicate that the integration of nahwu, sharaf, and balaghah forms a conceptual pedagogical framework that supports linguistic accuracy, semantic understanding, and communicative effectiveness in Arabic learning. Furthermore, contemporary educational studies demonstrate that combining classical linguistic principles with interactive and technology-enhanced instructional strategies improves student engagement, critical thinking, and language proficiency. The novelty of this study lies in proposing a conceptual model of integrated nahwu–sharaf–balaghah as a pedagogical foundation for twenty-first-century Arabic language education. This model bridges classical linguistic scholarship and modern educational innovation, contributing to curriculum development and sustainable Arabic language instruction in contemporary global contexts